TEMPERATURE CHANGES ON THE EXTERNAL ROOT SURFACE DURING POST SPACE PREPARATION (in vitro study) - Elka Radeva; Desislava Tsanova-Tosheva; Alexander Bonchev; Natali Tsvetanova; Tsvetelina Damyanova; Aysel Farieva; Sonya Georgieva; Iliyan Stoyanov (Peytchinski Publishing, 2017)
Purpose: The aim of this study is to investigate the temperature changes of the external root surface which occur during post space preparation with Peeso reamers at two different speeds. Materials and methods: Twenty nine extracted single rooted human teeth were used. The tooth crown was removed and the length of the roots was standardized at 15 mm. Then each root canal was prepared with Revo-S Ni-Ti rotary system and filled with sealer and gutta-percha by cold lateral condensation technique. The teeth were divided into three groups: Group 1 (n=12) - post space preparation was performed at 2800 rpm. Group 2 (n=12) - post space preparation was performed at 4700rpm. Control group (n=5) - without post space preparation. Two thermocouples were connected to the outer surface of the root at 4 mm and 8 mm from the coronal part. During post space preparation, the temperature rises were measured using two digital thermometers which registered the temperature changes at 10s, 20s and 30s. Statistical analysis was performed. Results: In the first 10 seconds of the preparation a slight increase of the temperature (1-2°C) was observed in the two points of the root surface where the thermocouples were attached to the roots of both groups. In the period from start to 20s the temperature of the teeth prepared with higher speed increased by 4.9°C compared to the teeth prepared at lower speed- the temperature increased by 3.6°C. Between the beginning point and the 30s the increasing of the temperature was higher - 9.1°C in group 2. Conclusion: In both groups, the temperature on the external root surface increased during post space preparation. The higher speed of the Peeso reamers might reach a critical level of 10 degrees on the external root surface which might lessen the possibility of a successful outcome of the endodontically treated teeth.